Rekonstruksi Epistemologis Pendidikan Bahasa Arab di Era Disruptif - Rifqi Aulia Rahman; Indah Kumalasari (Armala, 2020)
This study departs from the phenomena which are the eternal problems of Arabic education in Indonesia. These problems include that Arabic is still the scourge of most students in schools and colleges, curriculum design that still looks uniformity elements at many levels of school, incompetent and professional teachers, methods and learning strategies are monotonous, evaluation is not comprehensive, and many other componential things that are often found in Arabic education in the classroom. This review literature study offers a solution to the problem, not just looking at it from the narrow point of view of the learning components, but is more extensive and fundamental. It can begin with the reorientation of Arabic education itself epistemologically, considering short-term or long-term opportunities for Arabic education in Indonesia. This study also suggests holistic and synergistic problem-solving solutions, because all components in Arabic education are integral and interconnected.